High-strength hot-dip galvanized steel sheet having excellent plating quality, steel sheet for plating, and method for producing same
By forming a specific Mn and Si component concentration curve on the plating steel plate of a high-strength hot-dip galvanized steel plate and annealing in a reducing atmosphere with low dew point, the problems of poor plating quality and plating peeling are solved, and high Excellent surface quality and defect-free alloying heat treatment effect of the galvanized steel plate with strength hot-dip galvanized steel plate.
Patent Information
- Application Number
- CN202380045165.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, when manufacturing high-strength hot-dip galvanized steel sheets, the plating quality is poor, and problems of unplating and coating peeling are prone to occur, especially linear defects may occur after alloying heat treatment.
By forming a specific concentration curve of Mn and Si components on the plating steel plate, forming a pre-plating layer and annealing in a reducing atmosphere with low dew point, the oxygen content in the Fe plating layer is controlled, and the internal oxidation of Mn and Si is ensured, thereby inhibiting it. The surface diffuses to form a defect-free hot-dip galvanized steel plate.
It significantly improves the plating quality and adhesion during hot-dip galvanizing, prevents the plating layer from peeling, ensures excellent surface quality of the alloyed hot-dip galvanized steel sheet, and avoids the occurrence of linear defects.
Smart Images

Figure CN119256117A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a high-strength hot-dip galvanized steel sheet with excellent plating quality, a plated steel sheet for producing the high-strength hot-dip galvanized steel sheet, and methods for producing the same. Background Art
[0002] In recent years, in the automobile industry, high-strength steel sheets have been used as automobile steel materials to improve safety and reduce weight by reducing thickness. Martensitic steel and TRIP steel have been developed as preferred steel materials for automobiles. These high-strength steels are added with various alloy elements compared to ordinary steels, and in particular, many elements with a higher oxidation tendency than Fe, such as Mn, Si, Al, Cr, and B, are added.
[0003] The quality of hot-dip galvanizing is determined by the surface state of the annealed steel sheet before plating. The elements such as Mn, Si, Al, Cr, and B added to ensure the physical properties of the steel sheet cause the formation of surface oxides during the annealing process, thereby deteriorating the plating property. That is, during the annealing process, the elements diffuse to the surface and react with the trace amount of oxygen or water vapor present in the annealing furnace to form a single oxide or a composite oxide of the elements on the surface of the steel sheet, thereby reducing the reactivity of the surface. The annealed steel sheet surface with reduced reactivity will hinder the wettability of the hot-dip galvanizing bath, resulting in unplated areas where the plating metal is not attached locally or entirely on the surface of the plated steel sheet. In addition, due to these oxides, the formation of the alloying inhibition layer (Fe2Al5) necessary to ensure the adhesion of the coating during the hot-dip plating process is insufficient, thereby greatly reducing the plating quality of the plated steel sheet, such as the occurrence of coating peeling.
[0004] Various technologies for improving the plating quality of high-strength hot-dip plated steel sheets have been proposed. Among them, Patent Document 1 proposes a technology that controls the air-fuel ratio of air to fuel to 0.80 to 0.95 during annealing, oxidizes the steel sheet in a direct flame furnace in an oxidizing atmosphere, thereby forming iron oxides containing a single oxide or a composite oxide of Si, Mn or Al at a predetermined depth inside the steel sheet, and then performs reduction annealing of the iron oxide in a reducing atmosphere, and then performs hot-dip galvanizing, thereby providing a hot-dip galvanized steel sheet or an alloyed hot-dip galvanized steel sheet with excellent plating quality.
[0005] As in Patent Document 1, when a method of performing oxidation followed by reduction in an annealing process is used, components with a high affinity for oxygen, such as Si, Mn, and Al, are internally oxidized at a predetermined depth from the surface of the steel sheet, thereby suppressing diffusion to the surface layer, and thus the single oxide or composite oxide of Si, Mn, or Al on the surface layer is relatively reduced, thereby improving wettability with zinc, and thus reducing unplated areas. However, in the case of a steel type to which Si is added, Si is enriched just below the iron oxide during the reduction process, thereby forming a band-shaped Si oxide, and thus peeling occurs in the surface layer portion including the plated layer, that is, peeling occurs at the interface between the reduced iron and the base iron below, and thus there is a problem that it is difficult to ensure the adhesion of the plated layer.
[0006] In addition, as another method for improving the coating property of high-strength hot-dip plated steel sheets, Patent Document 2 proposes a method of maintaining a high dew point in the annealing furnace to internally oxidize easily oxidizable alloy components such as Mn, Si, and Al inside the steel, thereby reducing the oxides externally oxidized on the surface of the steel sheet after annealing to improve the coating property. However, the method according to Patent Document 2 can solve the coating property problem caused by the external oxidation of Si that is easily internally oxidized, but when a large amount of Mn that is relatively difficult to internally oxidize is added, there is a problem that the effect is minimal.
[0007] In addition, even if the plating property is improved by internal oxidation, linear non-plating may occur due to uneven surface oxides formed on the surface, or when alloyed hot-dip galvanized steel sheet (GA steel sheet) is manufactured by alloying heat treatment after plating, linear defects caused by uneven alloying may occur on the surface of the alloyed hot-dip galvanized steel sheet.
[0008] Another prior art is to perform Ni pre-plating before annealing to inhibit the diffusion of alloy elements to the surface during annealing. However, although this method is effective in inhibiting the diffusion of Mn, it has the problem of not being able to fully inhibit the diffusion of Si.
[0009] [Prior art literature]
[0010] [Patent Document]
[0011] (Patent Document 1) Korean Patent Publication No. 2010-0030627
[0012] (Patent Document 2) Korean Patent Publication No. 2009-0006881 Summary of the invention
[0013] 1. Technical issues to be resolved
[0014] According to one aspect of the present invention, there is provided a hot-dip galvanized steel sheet having excellent plating quality with no unplated coating and no peeling of the plating layer, and a method for producing the same.
[0015] According to another aspect of the present invention, a hot-dip galvanized steel sheet and a method for manufacturing the same are provided, wherein the hot-dip galvanized steel sheet does not generate linear defects even when alloying heat treatment is performed after plating, thereby being able to produce an alloyed hot-dip galvanized steel sheet having excellent surface quality.
[0016] According to another aspect of the present invention, there is provided a steel sheet for plating and a method for manufacturing the same, the steel sheet for plating being capable of manufacturing a hot-dip galvanized steel sheet having excellent plating quality as described above.
[0017] The technical problems of the present invention are not limited to the above contents. Those skilled in the art to which the present invention belongs can easily understand the additional technical problems of the present invention from the overall content of this specification.
[0018] (II) Technical solution
[0019] According to one aspect of the present invention, a plated steel sheet has a composition comprising, in weight %, Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, Cr: 1.5% or less, B: 0.005% or less, the balance Fe and inevitable impurities, and a GDS curve of the Mn component and a GDS curve of the Si component observed in a depth direction from the surface respectively include a maximum point and a minimum point in sequence. The difference between the value obtained by dividing the Mn concentration at the maximum point of the GDS curve of the Mn component by the Mn concentration of the base material and the value obtained by dividing the Mn concentration at the minimum point of the GDS curve of the Mn component by the Mn concentration of the base material (the converted concentration difference of Mn) can be 10% or more, and the difference between the value obtained by dividing the Si concentration at the maximum point of the GDS curve of the Si component by the Si concentration of the base material and the value obtained by dividing the Si concentration at the minimum point of the GDS curve of the Si component by the Si concentration of the base material (the converted concentration difference of Si) can be 10% or more.
[0020] When no local point appears within a depth of 5 μm, the position at a depth of 5 μm is regarded as the position where the local point appears.
[0021] A hot-dip galvanized steel sheet according to another aspect of the present invention may include the above-mentioned steel sheet for plating and a hot-dip galvanized layer formed on the steel sheet for plating.
[0022] A method for manufacturing a plated steel sheet according to another aspect of the present invention may include the following steps: preparing a base iron having a composition, in weight %, of Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, Cr: 1.5% or less, B: 0.005% or less, the balance of Fe and inevitable impurities; electroplating the base iron to form a Fe coating containing 5-50 weight % of oxygen; and annealing the base iron on which the Fe coating is formed in an annealing furnace having an atmosphere of 1-70% H2-balance N2 gas with a dew point temperature controlled below -20°C for 5-120 seconds.
[0023] A method for manufacturing a hot-dip galvanized steel sheet according to another aspect of the present invention may include the following steps: preparing a base iron having a composition, in weight %, of Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, Cr: 1.5% or less, B: 0.005% or less, the balance of Fe and inevitable impurities; electroplating the base iron to form a Fe plating layer containing 5-50 weight % of oxygen; annealing the base iron forming the Fe plating layer at 600-950° C. for 5-120 seconds in an annealing furnace having an atmosphere of 1-70% H2-balance N2 gas with a dew point temperature controlled at less than -20° C., thereby obtaining a plated steel sheet; and immersing the plated steel sheet in a galvanizing bath.
[0024] (III) Beneficial effects
[0025] As described above, the present invention can provide a hot-dip galvanized steel sheet that significantly improves the non-plating phenomenon that occurs during hot-dip galvanizing and improves the plating adhesion by forming a pre-plating layer and controlling the concentration profile of the internal Mn and Si components.
[0026] In addition, according to one aspect of the present invention, even if the hot-dip galvanized steel sheet of the present invention is subjected to alloying heat treatment, linear defects on the surface of the obtained alloyed hot-dip galvanized steel sheet can be prevented, thereby providing an alloyed hot-dip galvanized steel sheet with excellent surface quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the GDS curve of Mn and Si components measured after removing the coating of a hot-dip galvanized steel sheet made of a cold-rolled steel sheet electroplated with Fe.
[0028] Figure 2 Schematic diagram showing the annealing process of a base steel sheet on which an oxygen-containing Fe plating layer is formed. DETAILED DESCRIPTION
[0029] Hereinafter, a high-strength hot-dip galvanized steel sheet having excellent plating quality according to one aspect of the present invention completed by the inventor's research is described in detail. It should be noted that when the concentration of each element is expressed in the present invention, it is expressed by weight % unless otherwise defined. In addition, the Fe electroplating amount is the plating amount measured by the total amount of Fe contained in the coating per unit area, and oxygen and unavoidable impurities in the coating are not included in the plating amount.
[0030] In addition, unless otherwise defined, the concentration and concentration curve mentioned in the present invention refer to the concentration and concentration curve measured by using GDS, that is, using a glow discharge optical emission spectrometer.
[0031] Hereinafter, the present invention will be described in detail.
[0032] It is known that the reason why non-plating and reduced plating adhesion occur in steel sheets containing a large amount of Mn and Si is due to surface oxides generated by oxidation of alloy elements such as Mn and Si on the surface during annealing of the cold-rolled steel sheets at high temperatures.
[0033] As a method for suppressing the diffusion of alloying elements such as Mn and Si to the surface to form an oxide layer containing a large amount of oxygen, a redox method of oxidizing during the heating process and then maintaining it in a reducing atmosphere for reduction or a method of coating the surface of the base metal with iron oxide and performing heat treatment can be used. However, the iron oxide firmly formed on the surface of the base metal contains not only FeO but also Fe3O4 and Fe2O3 that are difficult to reduce, and the surface is reduced to metallic iron during annealing in a reducing atmosphere. On the other hand, the reduction rate of the interface between the iron oxide layer and the base iron is slow, so it is difficult to completely reduce, and the oxides of Mn and Si accumulate at the interface to form a continuous oxide layer. Therefore, although the wettability with molten zinc can be improved, the oxide layer is easily broken and the problem of plating peeling may occur.
[0034] In addition, when an annealing internal oxidation method is used in which alloying elements such as Mn and Si are oxidized inside the steel by increasing the oxygen partial pressure or dew point in the annealing furnace during the heat treatment process, Mn and Si oxides are preferentially formed on the surface of the steel during the heat treatment process, and then Mn and Si are oxidized by oxygen diffused into the steel, thereby inhibiting surface diffusion. Therefore, a thin oxide film is formed on the surface of the base iron, and when the surface of the cold-rolled steel sheet before annealing is not completely homogeneous or there are local deviations in oxygen partial pressure, temperature, etc., there is a tendency to cause linear defects that can be easily recognized by visual inspection when the wettability is uneven during hot-dip galvanizing and non-plating occurs, or when the thickness of the oxide film is uneven during the alloying heat treatment after galvanizing and a difference in the degree of alloying occurs.
[0035] In order to solve the above technical problems, the present inventors attempted to manufacture a hot-dip galvanized steel sheet having a fine surface and free from the problem of plating peeling by controlling the existence form of Mn and Si as oxidizing elements on the surface side of the steel sheet for plating as follows.
[0036] That is, the GDS concentration curve of Mn and Si of the steel sheet according to one specific embodiment of the present invention may have the following characteristics. Figure 1 The GDS curve of the present invention is used to explain the steel sheet for coating in detail.
[0037] Figure 1 This is a diagram schematically showing a typical GDS curve of alloy components that may appear from the surface after the zinc coating layer is removed from a hot-dip galvanized steel sheet including the steel sheet of the present invention and a GDS curve of alloy components that are not within the scope of the present invention. In the figure, the vertical axis represents the concentration of alloy elements such as Mn and Si, and the horizontal axis represents the depth.
[0038] from Figure 1 From the typical example of the GDS curve of the Mn component of the present invention shown, it can be seen that the steel plate of the present invention can have a very low Mn concentration on its surface, and a concentration gradient in the form of a maximum point and a minimum point appearing in sequence from the surface in the depth direction. The sequential appearance here does not mean that the maximum point must appear first in the depth direction from the surface (interface). Depending on the situation, the minimum point may appear first, but this means that the maximum point and the minimum point will appear in sequence later. However, in some specific embodiments, the minimum point may not appear. In this case, the internal concentration of the area with a depth of 5μm can be set to the minimum point concentration. In addition, the concentration of the alloying element on the surface can have a value less than the concentration of the maximum point, but depending on the situation, a minimum point with a low concentration of the alloying element may also appear between the surface and the maximum point.
[0039] In using the Figure 1In the illustrated GDS concentration curve, although not necessarily limited to this, the surface layer portion corresponds to the Fe plating where the alloy element does not diffuse in large quantities from the base iron and the concentration of the alloy element is low, the maximum point corresponds to the region where the internal oxide of the alloy element formed near the interface between the Fe plating and the base iron is concentrated, and the minimum point appearing on the base iron side in the Fe plating corresponds to the region where the alloy element diffuses into the Fe plating that does not contain the alloy element and is diluted, or the alloy element diffuses to the maximum point where internal oxidation occurs and is depleted.
[0040] In a specific embodiment of the present invention, the maximum point can be formed at a depth of 0.05-1.0 μm from the surface of the steel plate. When the maximum point appears in an area deeper than this depth, it may not be judged as a maximum point caused by the effect of the present invention. In addition, the minimum point can be formed at a position within a depth of 5 μm from the surface of the steel plate. As described above, when the minimum point is not formed at a position within a depth of 5 μm, the depth of 5 μm can be set as the position where the minimum point is formed. The concentration at a depth of 5 μm is substantially the same as the concentration of the base material, so it can be regarded as a position where the concentration no longer decreases.
[0041] At this time, in the Mn concentration curve and the Si concentration curve, the greater the difference between the converted concentration of the element at the maximum point (the value obtained by dividing the concentration at the position by the concentration of the base material, expressed in %) and the converted concentration at the minimum point, the less Mn and Si diffused to the surface can be, so it is important. In a specific embodiment of the present invention, the values of the maximum point converted concentration-minimum point converted concentration of Mn and Si can be 10% or more respectively.
[0042] The results of the experiments conducted by the inventors under various conditions show that when the above conditions are met, a hot-dip galvanized steel sheet can be obtained that does not undergo unplating during hot-dip galvanizing and has good coating adhesion. However, when the difference between the conversion concentrations of the maximum and minimum points of Mn and Si is less than 10%, there may be a problem of point-like or linear unplating or coating peeling. That is, by controlling the difference between the conversion concentrations to be above the specified level, it is possible to prevent the generation of Mn and Si oxides on the surface, thereby manufacturing an ultra-high strength hot-dip galvanized steel sheet with a beautiful surface and good coating adhesion, and even if it is subsequently subjected to an alloying heat treatment process, defects such as linear defects on the surface can be suppressed. The greater the difference between the conversion concentration values, the more advantageous it is, so there is no need to set an upper limit for the value. However, considering the content of the elements contained, the difference between the conversion concentration values of Mn and Si can be set to less than 200%. In another specific embodiment of the present invention, the conversion concentration difference between Mn and Si can be set to more than 15% or more than 20%.
[0043] Hereinafter, the GDS analysis method performed in the present invention will be described in detail.
[0044] For GDS concentration analysis, the hot-dip galvanized steel sheet is cut into a length of 30-50 mm and immersed in a 5-10 wt% hydrochloric acid aqueous solution at a room temperature of 20-25°C to remove the galvanized layer. In order to prevent damage to the surface of the base iron during the dissolution of the galvanized layer, when the generation of bubbles caused by the reaction of the galvanized layer and the acid solution stops, the acid solution is removed within 10 seconds, and the base iron is washed with pure water and dried. Of course, if the steel sheet is not hot-dip galvanized, the analysis can be performed even without such removal of the coating.
[0045] The GDS concentration curve measures the concentration of all components contained in the steel plate at intervals of 1-5 nm in the thickness direction of the steel plate. The measured GDS curve may contain irregular noise. In order to calculate the maximum and minimum points of Mn and Si concentrations, a Gaussian filter with a cutoff value of 100 nm is applied to the measured concentration curve to obtain an average concentration curve, and the concentration values and depths of the maximum and minimum points of the concentration are respectively obtained from the noise-removed curve. In addition, it should be noted that the maximum and minimum points mentioned in the present invention are calculated as maximum and minimum points only when they differ from each other by more than 10 nm in the depth direction.
[0046] The plated steel sheet used as the subject of the present invention may include a base iron and an Fe plating layer formed on the base iron. The composition of the base iron is not particularly limited.
[0047] However, when the high-strength steel sheet contains 1.0-8.0 wt % of Mn and 0.05-3.0 wt % of Si and has a composition that is easy to generate oxides on the surface, the coating property can be advantageously improved by the present invention. The upper limit of the Mn concentration of the substrate iron is not particularly limited, but considering the commonly used composition, the upper limit can be limited to 8 wt %. In addition, the lower limit of the Mn concentration is not particularly limited, but in the case of a composition containing less than 1.0 wt %, even if the Fe coating is not formed, the surface quality of the hot-dip galvanized steel sheet is also very fine, so there is no need to perform Fe electroplating. The upper limit of the Si concentration is not particularly limited, but considering the commonly used composition, the upper limit of the Si concentration can be limited to less than 3.0 wt %, and when the Si concentration is less than 0.05 wt %, even if the method of the present invention is not performed, the quality of hot-dip galvanizing is also very fine, so there is no need to perform the method of the present invention.
[0048] The Mn and Si mentioned above are elements that affect the plating properties, and therefore their concentrations may be limited as described above. However, the present invention does not particularly limit the other components of the base material iron.
[0049] However, considering that in the case of a high-strength steel sheet containing a large amount of alloy components, serious unplating and reduction in plating adhesion may occur, in a specific embodiment of the present invention, the composition of the base iron may include, by weight%, Mn: 1.0-8.0%, Si: 0.05-3.0%, C: 0.06-0.4% (preferably 0.07-0.4%, more preferably 0.08-0.4%), Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, N: 0.01% or less, Cr: 1.5% or less, B: 0.005% or less, the balance Fe and inevitable impurities. P, S and N are impurities, and the less they are added, the more advantageous it is. Cr and B are optional elements, and it is not harmful even if they are not added, so the lower limit is not individually defined.
[0050] The composition of the steel of the present invention will be described in more detail below. Unless otherwise indicated, the content of each element is based on weight.
[0051] Mn: 1.0-8.0%
[0052] Manganese (Mn) is an element added to ensure strength. When the Mn content is less than 1.0%, it is difficult to ensure strength. On the other hand, when the Mn content exceeds 8.0%, the bainite phase transformation rate slows down, too much new martensite is formed, and it is difficult to obtain high hole expansion. In addition, due to the segregation of Mn, a banded structure is formed, which impairs the material uniformity and formability of the material. Therefore, the Mn content is preferably in the range of 1.0-8.0%. The lower limit of the Mn content is more preferably 1.5%.
[0053] Si: 0.05-3.0%
[0054] Silicon (Si) is a useful element for improving the strength of steel sheets by solid solution strengthening and precipitation hardening. The silicon (Si) inhibits the formation of cementite, and therefore has the effect of promoting C enrichment in austenite, and is an essential element for improving the strength and elongation of steel by generating retained austenite after annealing. When the content of Si exceeds 3.0%, the physical properties of the weld are deteriorated due to LME cracks, and the surface characteristics and coating properties of the steel are deteriorated. Therefore, the content of Si preferably has a range of 0.05-3.0%.
[0055] C: 0.06-0.4%
[0056] Carbon (C) is an element that ensures the strength of steel by solid solution strengthening and precipitation strengthening, and is an effective element that ensures high ductility by stabilizing retained austenite. When the C content is less than 0.05%, a tensile strength of 1500MPa cannot be obtained, and when the C content exceeds 0.4%, a steel sheet cannot be manufactured by cold rolling. Therefore, the C content is preferably 0.06-0.4%. On the other hand, the C content is more preferably in the range of 0.2% or more and 0.4% or less.
[0057] Al: 0.005-3.0%
[0058] Aluminum (Al) is an element having a deoxidizing effect on molten steel, and similarly to Si, plays a role in improving the stability of austenite, and is effective in improving elongation.
[0059] When the Al content is less than 0.005%, deoxidation of the steel cannot be fully achieved, and the cleanliness of the steel is impaired. On the other hand, when the Al content is too much, the phase transformation temperature rises significantly, and the fraction of ferrite increases, so that high strength cannot be achieved. Therefore, the Al content is set to 3.0% or less. In another specific embodiment of the present invention, the Al may be limited to 2.0% or less, or the Al may be limited to 1.0% or less.
[0060] P: 0.04% or less
[0061] Phosphorus (P) is contained as an impurity and segregates at the grain boundaries, thereby reducing toughness. Therefore, it is preferred to control the phosphorus content as low as possible. In addition, when the P is added excessively, the toughness of the steel material deteriorates, so in order to prevent this in the present invention, it is preferred to limit the upper limit of the P to 0.04%. In the present invention, the less P is added, the more advantageous it is, so there is no need to specifically set a lower limit for the P content. However, considering conventional manufacturing methods, the lower limit of the P content may also be set to 0.002%. In a specific embodiment of the present invention, the upper limit of the P content may also be set to 0.0173%.
[0062] S: 0.01% or less
[0063] Similar to P, sulfur (S) is contained in steel as an impurity. S combines with Mn to form inclusions, which may reduce hole expandability and may also reduce weldability and hot rolling properties, so it is advantageous to control the sulfur content as low as possible. Therefore, considering the situation where S is inevitably included, the S content can be limited to less than 0.01%. In the present invention, the less S is added, the more advantageous it is, so there is no need to specifically set a lower limit for the S content. However, considering conventional manufacturing processes, the lower limit of the S content can also be set to 0.0009%. In another specific embodiment of the present invention, the upper limit of the S content can be set to 0.0021%.
[0064] N: 0.01% or less
[0065] In the present invention, nitrogen (N) is contained in the steel as an impurity, and it is advantageous to control the content of the nitrogen (N) to be as low as possible. Therefore, in a specific embodiment of the present invention, the N can be limited to less than 0.01%, and the lower limit is not particularly set. However, considering the situation where N is inevitably included, 0% (i.e., more than 0%) can be excluded. In another specific embodiment of the present invention, the lower limit of the N content can also be set to 0.0005%. In addition, in another specific embodiment of the present invention, the upper limit of the N content can be set to 0.007%, or it can be set to 0.006% or 0.0052%.
[0066] Cr: less than 1.5%
[0067] Chromium (Cr) is an effective element for improving strength. The chromium (Cr) suppresses the formation of carbides, making it easy to ensure retained austenite. On the other hand, when the Cr content exceeds 1.5%, local corrosion resistance deteriorates and surface oxides are formed, thereby impairing phosphate treatment properties. Therefore, the Cr content preferably has a range of 1.5% or less. The Cr content is more preferably 1.0% or less.
[0068] B: 0.005% or less
[0069] Boron (B) strengthens the grain boundaries and suppresses the ferrite phase transformation during the cooling process after annealing. In order to obtain this effect, the addition amount of B can be set to 0.0001% or more. When the addition amount of B is too much, the hot rolling property is reduced, and B accumulates excessively on the surface, thereby hindering the plating property. Therefore, the B content preferably has a range of 0.005% or less.
[0070] In the present invention, high strength means a case where high strength is obtained after annealing, and also includes a case where high strength can be obtained through heat treatment in subsequent processes. In addition, in the present invention, high strength may refer to a tensile strength of 490 MPa or more, but is not limited thereto. In addition to the above-mentioned components, the base iron may further contain elements such as Ti, Mo, Nb, etc., totaling less than 1.0%. There is no particular limitation on the base iron, but in a specific embodiment of the present invention, a cold-rolled steel sheet or a hot-rolled steel sheet may be used as the base iron. In addition, although not necessarily limited thereto, in a specific embodiment, the cold-rolled steel sheet or the hot-rolled steel sheet may use martensitic steel or TRIP steel.
[0071] In a specific embodiment of the present invention, the cold-rolled steel sheet or the hot-rolled steel sheet may have a fine structure, and the fine structure includes: 30-70 volume % of tempered martensite, 5-45 volume % of bainite, 10-40 volume % of retained austenite, and 20 volume % or less of ferrite phase. The fine structure can have high strength while ensuring hole expansion by including more than 30 volume % of tempered martensite. In addition, when more than 10 volume % of retained austenite is included, the phase transformation induced plasticity phenomenon caused by the retained austenite can be utilized, thereby greatly improving the elongation. Bainite is included to form retained austenite and ensure strength, and more than 5 volume % of bainite needs to be included. Ferrite can be included as needed to improve mechanical properties by improving elongation and refining old austenite grains, and stabilize the retained austenite by increasing the C enrichment in the retained austenite. However, when the proportion of the ferrite phase exceeds 20% by volume, the interphase hardness difference with the tempered martensite as the matrix structure becomes large, and the bendability and hole expandability may deteriorate, so the proportion of the ferrite phase may be limited to 20% by volume or less. Depending on the situation, the ferrite phase may be contained in an amount of 3% by volume or more. When the proportion of each phase is too high, the proportion of other phases may be limited to less than an appropriate range, so the upper limit may be limited as described above.
[0072] The hot-rolled steel sheet or cold-rolled steel sheet having the above-mentioned fine structure is not necessarily limited thereto, but can be manufactured by the following process.
[0073] That is, a hot rolled steel plate can be manufactured by a process comprising the following steps: heating a steel billet, wherein the steel billet contains, in weight %, Mn: 1.0-8.0%, Si: 0.05-3.0%, C: 0.06-0.4% (preferably 0.07-0.4%, more preferably 0.08-0.4%), Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, N: 0.0% or less, Cr: 1.5% or less, B: 0.005% or less, the balance Fe and inevitable impurities; hot rolling the heated steel billet to obtain a steel plate; and coiling the hot rolled steel plate. In addition, in the case of a cold-rolled steel sheet, it can be manufactured by a process comprising the following steps: cold rolling the hot-rolled steel sheet; keeping the cold-rolled steel sheet in a soaking zone (soaking section) for 50-500 seconds; cooling the kept steel sheet at a cooling rate of more than 1°C / second (depending on the situation, it can be limited to less than 3000°C / second, less than 2000°C / second or less than 1000°C / second) to a temperature between 100-300°C; heating the cooled steel sheet to a temperature between 300-600°C and keeping it for more than 50 seconds (depending on the situation, it can be limited to less than 3000 seconds or less than 2000 seconds).
[0074] In one aspect of the present invention, a hot-dip galvanized steel sheet including the plated steel sheet may be provided, and the hot-dip galvanized steel sheet may include the plated steel sheet and a hot-dip galvanized layer formed on the surface of the plated steel sheet. In this case, any commonly used hot-dip galvanized steel sheet may be used as the hot-dip galvanized steel sheet, and the type thereof is not particularly limited.
[0075] Next, an exemplary specific embodiment of a method for manufacturing a plated steel sheet and a hot-dip galvanized steel sheet having the above-mentioned advantageous effects is described. According to a specific embodiment of the present invention, the plated steel sheet can be manufactured by a process comprising the following steps: preparing a base iron; electroplating the base iron to form an Fe plating layer containing 5-50 wt % of oxygen; annealing the base iron forming the Fe plating layer to obtain a plated steel sheet.
[0076] Fe plating containing 6.2 wt% of oxygen was performed on a 1.2 GPa grade cold rolled steel sheet (martensitic steel) containing 2.3% of Mn, 0.9% of Si and other alloying elements to obtain an Fe deposition amount of 2.03 g / m 2 , and then the electroplated cold-rolled steel sheet was annealed for 53 seconds in an atmosphere of N2-5% H2, a dew point of -40°C, and a temperature of 800°C, and then cooled. The same atmosphere was maintained throughout the annealing process, and when a sample was collected from the cooled steel sheet and the cross section was observed using a transmission electron microscope, it was confirmed that granular Mn and Si oxides were formed at the interface between the iron electroplating layer and the base iron, and on the other hand, it was confirmed that almost no Mn and Si oxides were formed on the surface of the electroplating layer. In particular, when this state was analyzed using a GDS curve, as shown in FIG. Figure 1 As shown, the maximum values of Mn and Si concentrations may appear just below the surface of the steel plate (including the Fe coating), while the minimum values of Mn and Si concentrations may appear at a deeper position. Of course, depending on the situation, the minimum value may not appear clearly, and the concentration may show a tendency to gradually decrease, but the maximum value can be clearly observed.
[0077] This phenomenon is because the Fe plating layer with a high oxygen content is formed before annealing. That is, when the Fe electroplating layer contains 5-50 wt% of oxygen, when annealing is performed in an annealing furnace in a reducing atmosphere, the oxygen in the Fe electroplating layer will oxidize the alloying elements such as Mn and Si that diffuse from the base iron to the surface and accumulate at the interface between the Fe electroplating layer and the base iron. Therefore, if Figure 1As shown in the graph, when using GDS to measure concentration, the high maximum point of the concentration of Mn, Si, etc. is confirmed at the depth equivalent to the thickness of the iron electroplating layer from the surface. In addition, even if the concentration of alloying elements such as Mn with slow diffusion rate is diluted by the iron electroplating layer or the Mn in solid solution is exhausted due to internal oxidation, it is also impossible to diffuse rapidly from the substrate iron, so there may be a minimum point after the GDS concentration maximum point. However, Si diffuses rapidly from the inside during annealing, and continues to be internally oxidized and accumulate oxides at the interface of the iron electroplating layer and the substrate iron, so it may not be possible to confirm the minimum point in the GDS concentration analysis. Therefore, the absence of a minimum point in the GDS concentration curve indicates that alloying elements such as Mn and Si are oxidized by the iron electroplating layer and effectively inhibit diffusion to the surface.
[0078] Unlike oxides firmly formed at high temperatures, when an iron coating containing a large amount of oxygen is formed and annealed, reduction occurs not only on the surface of the iron electroplated layer, but also at the interface between the iron electroplated layer and the base steel sheet. At this time, the reduced iron diffuses and joins with the base iron, and Mn and Si react with the oxygen in the Fe coating to form granular or discontinuous plate-like oxides at the interface between the iron electroplated layer and the base steel sheet, so that good adhesion can be maintained between the iron electroplated layer and the base metal. In addition, the uniformly formed iron electroplated layer suppresses the generation of surface oxides, reduces the concentration of alloying elements such as Mn and Si dissolved on the surface of the steel sheet, and promotes the alloying reaction with the zinc coating, so that a uniform alloyed hot-dip plated steel sheet without surface defects can be obtained.
[0079] Unlike the redox method, the annealing internal oxidation method does not form a layered oxide layer, so when hot-dip galvanizing is performed on ultra-high strength steel sheets containing a large amount of alloying elements such as Mn and Si, it shows excellent characteristics in improving the coating adhesion. However, the water vapor in the annealing furnace will inevitably preferentially oxidize the surface of the steel sheet, and then oxygen will penetrate into the interior, so the surface oxide cannot be fundamentally removed. As a result, when the surface of the cold-rolled steel sheet before annealing is not completely homogeneous or when local deviations in oxygen partial pressure, temperature, etc. occur during annealing, the wettability with the hot-dip galvanizing solution is uneven, resulting in non-plating, or the thickness of the oxide film is uneven during the alloying heat treatment after galvanizing, resulting in differences in the degree of alloying, so there may be a problem of causing linear defects that can be easily recognized by visual inspection.
[0080] In order to suppress the surface diffusion of alloy elements by Fe plating containing a large amount of oxygen to produce a fine hot-dip galvanized steel sheet without the problem of plating peeling, it is preferred to form an iron electroplating layer containing 5-50 wt% of oxygen on the base iron so that the Fe plating amount based on the iron adhesion amount is 0.5-3.0 g / m 2The steel sheet is coated with Fe and heated to a temperature of 600-950°C to ensure the mechanical and physical properties of the steel sheet. The steel sheet is cooled again and hot dipped.
[0081] In a specific embodiment of the present invention, the Fe coating can be formed by a continuous coating process, and based on the Fe adhesion amount, the Fe coating amount at this time can be 0.5-3.0 g / m 2 When the Fe coating amount is less than 0.5g / m 2 When the amount of Fe plating exceeds 3.0 g / m, the effect of suppressing the diffusion of alloy elements by Fe plating in the usual continuous annealing process may be insufficient. 2 , and the inhibition effect of alloying elements can be further improved. However, in order to ensure a high plating amount, multiple plating units need to be used, and when an insoluble anode is used, the electroplating solution will quickly acidify and reduce the plating efficiency, and there is a problem of sludge generation, so it is not economical. In another specific embodiment of the present invention, the Fe plating amount can be 1.0-2.0 g / m 2 When the Fe coating is formed and internal oxidation is performed, internal oxides are formed at the interface between the Fe coating and the substrate iron or just below the interface, so the maximum points of Mn and Si concentration exist in the region of 0.05-1.0 μm. 2 The Fe plating amount may correspond to a thickness of 0.05-0.4 μm after annealing.
[0082] In addition, the Fe coating with the above-mentioned high oxygen concentration forms a maximum point and a minimum point in the GDS concentration curve of the Mn and Si elements inside the plated steel sheet by controlling the temperature, dew point temperature and atmosphere of the subsequent annealing process, and the converted concentration at the maximum point and the converted concentration at the minimum point can meet the numerical range limited in a specific embodiment of the present invention. Taking this into account, in a specific embodiment of the present invention, the oxygen concentration in the Fe coating can be 5-50% by weight, and in another specific embodiment, the oxygen concentration in the Fe coating can be 10-40% by weight. In order to obtain the effect of inhibiting surface oxides, the oxygen content in the Fe coating needs to be sufficient. Although the oxygen concentration in the Fe coating is less than 5% by weight, the effect of inhibiting surface oxides can also be obtained by increasing the Fe coating amount, but in order to obtain the above-mentioned effect, it is necessary to carry out more than 3.0 g / m 2of plating, so the above-mentioned various problems may occur. In addition, when the oxygen content does not reach 5 wt %, it is difficult to form a maximum point and a minimum point in the GDS curve of Mn and Si in sequence, so in a specific embodiment of the present invention, the oxygen content in the Fe coating is controlled to be more than 5 wt %. In addition, although the inhibitory effect of the surface oxide in the annealing process can be further increased as the oxygen concentration in the Fe coating increases, it is difficult to obtain a coating exceeding 50 wt % by a common electroplating method, so the upper limit of the oxygen concentration in the Fe coating can be limited to 50 wt %. In another specific embodiment of the present invention, the oxygen concentration in the Fe coating can be limited to 10-40%.
[0083] In a specific embodiment of the present invention, the annealing temperature can be 600° C. to 950° C. based on the temperature of the steel sheet in the soaking zone. When the annealing temperature is too low, the structure of the cold-rolled steel sheet cannot be properly restored and recrystallized, so it is difficult to ensure the mechanical and physical properties of the steel sheet, such as strength and elongation. When the annealing temperature exceeds 950° C., the alloy elements in the steel diffuse rapidly to the surface, resulting in poor quality of hot-dip galvanizing, and unnecessary operation at high temperature, which is uneconomical.
[0084] In addition, in a specific embodiment of the present invention, although not necessarily limited to this, the dew point inside the annealing furnace can be lower than -20°C. When the dew point temperature is maintained at less than -20°C, a separate humidifying device for increasing the dew point is not required, so it is economical. Moreover, in the case of the present invention, since an Fe plating layer with a high oxygen concentration is formed, even if internal oxidation through the atmosphere is not induced, the diffusion of alloy elements such as Mn and Si to the surface can be sufficiently prevented. The lower limit of the dew point temperature is not particularly limited. However, when the dew point is maintained at less than -90°C, it may be necessary to use very high purity gas, etc., which is industrially disadvantageous. In view of this, the lower limit of the dew point can be set to -90°C. According to another specific embodiment of the present invention, the dew point when the temperature of the steel plate is 600-950°C can be -70°C to -30°C.
[0085] In addition, in order to prevent oxidation of the substrate iron and the Fe coating during annealing, the hydrogen concentration in the atmosphere gas during annealing can be set to more than 1% by volume. When the hydrogen concentration is less than 1%, it is impossible to effectively oxidize and remove the trace oxygen inevitably contained in the H2 and N2 gases and increase the oxygen partial pressure, so it may cause surface oxidation of the substrate iron. In addition, when the hydrogen concentration exceeds 70%, the risk of explosion during gas leakage and the cost increase caused by high hydrogen operation, so the hydrogen concentration can be set to less than 70%. In addition to the hydrogen (H2), the gas other than the impurity gas inevitably contained can be nitrogen (N2) in essence.
[0086] In addition, according to a specific embodiment of the present invention, the holding time after reaching the target temperature during annealing can be limited to 5-120 seconds. In order to fully transfer heat to the inside of the base material iron during annealing to obtain uniform mechanical and physical properties in the thickness direction, it is necessary to keep it at the annealing target temperature for more than 5 seconds. In addition, when the high-temperature annealing holding time is too long, the diffusion of the alloy interfering elements through the Fe coating increases, thereby increasing the amount of surface oxides generated, resulting in a deterioration in the quality of hot-dip galvanizing, so the holding time can be limited to less than 120 seconds.
[0087] Below, refer to Figure 2 , the effect of suppressing the surface diffusion of Mn and Si during annealing of a cold-rolled steel sheet having an Fe-plated layer containing a large amount of oxygen formed based on the above content in a high dew point atmosphere is described in more detail.
[0088] Figure 2 The phenomenon occurring inside the steel plate when the temperature of the steel plate is increased according to the conditions of the present invention is schematically shown.
[0089] Figure 2 (a) is a schematic cross-sectional view showing a base steel plate on which a Fe plating layer containing a large amount of oxygen is formed. The base steel plate contains alloy elements such as Mn and Si, and the Fe plating layer contains 5-50 wt % of oxygen and impurities inevitably mixed in during the plating process, and the balance is composed of Fe.
[0090] Figure 2 (b) shows the state where the cold-rolled steel sheet electroplated with iron is heated to about 300-500°C in a nitrogen atmosphere containing 1-70% H2. The surface of the Fe-plated layer is gradually reduced, oxygen is removed, and internal oxides of Mn, Si, etc. diffused from the base iron begin to form at the interface between the Fe-plated layer and the base iron. As the temperature rises, the oxides at the grain boundaries grow coarsely.
[0091] Figure 2 (c) is a schematic cross-sectional view of the base steel plate when the temperature is raised to 500-700°C in the same reducing atmosphere. The Fe coating is almost mostly reduced to form ferrite with lower Mn and Si concentrations than the base iron, and the oxygen in the Fe coating is gradually depleted, so Mn and Si begin to penetrate the Fe coating and slowly diffuse to the surface of the Fe coating.
[0092] Figure 2(d) is a schematic cross-sectional view of a steel sheet annealed at a temperature of 600-950°C. In the iron electroplating layer, except for the internal oxides of Mn, Si, etc., the oxygen dissolved in the metal iron is completely removed, and the generated internal oxide is generally spherical or short plate-shaped. In addition, due to the growth of the grains, the iron electroplating layer can form a single grain with the substrate iron. However, the shape of the internal oxide does not necessarily have to be generated in a granular form, and depending on the elongation of the cold-rolled steel sheet, the steel composition, the atmosphere in the annealing furnace, and the oxygen content contained in the iron electroplating layer, the grains of the substrate iron and the grains of the iron electroplating layer can appear separately, and short linear oxides can be generated along the interface between the iron electroplating layer and the substrate iron or the grain boundaries inside the substrate iron.
[0093] After the annealing step, the annealed steel sheet may be cooled. The cooling conditions in the cooling step after the annealing step do not have a significant effect on the surface quality of the final product, that is, the coating quality, and therefore, there is no need to particularly limit the cooling conditions in the present invention. However, in order to prevent oxidation of the iron component during the cooling process, an atmosphere that is at least reducing to iron may be used.
[0094] According to a specific embodiment of the present invention, the steel sheet for coating obtained according to the above process can be hot-dip galvanized to form a hot-dip galvanized layer. In the present invention, the hot-dip galvanizing method is not particularly limited.
[0095] In the present invention, any base iron having the above alloy composition can be used as the base iron of the plated steel sheet or hot-dip galvanized steel sheet according to the present invention without limitation, and therefore the method for producing the base iron is not particularly limited.
[0096] In a specific embodiment of the present invention, the Fe plating layer can be formed on the surface of the substrate iron by electroplating, and the oxygen concentration of the formed Fe plating layer can be controlled by appropriately controlling the conditions of the electroplating solution and the plating conditions.
[0097] That is, in the present invention, in order to form the Fe plating layer, an electroplating solution can be used, which contains: iron ions, wherein the iron ions include divalent iron ions and trivalent iron ions; a complexing agent; and inevitable impurities, and the concentration of trivalent iron ions in the iron ions is 5-60% by weight.
[0098] According to a specific embodiment of the present invention, the electroplating solution includes ferrous iron and ferric iron. In order to obtain high plating efficiency, it can be advantageous to only include ferrous iron, but when only including ferrous iron, the solution deteriorates and the plating efficiency is sharply reduced, so that the quality deviation in the continuous electroplating process may be caused, so the ferric iron may be further included. At this time, the concentration of the ferric iron is preferably 5-60% by weight of the sum of ferrous iron and ferric iron, more preferably 5-40% by weight. When the concentration of the ferric iron is less than 5%, the speed at which ferric iron is reduced to ferrous iron in the negative electrode is less than the speed at which ferric iron is oxidized to ferric iron in the positive electrode, so the concentration of ferric iron rises sharply, pH sharply decreases, and plating efficiency continues to decrease. In addition, when the ion concentration of ferric iron exceeds 60%, the reaction amount of ferric iron reduced to ferrous iron in the negative electrode is greatly increased compared with the reaction amount of ferrous iron being reduced and precipitated as metallic iron, so plating efficiency is greatly reduced, and plating quality is reduced. Therefore, considering the equipment and process characteristics such as the coating amount, the working current density, the solution supply amount, the amount of solution lost due to adhesion to the strip, and the concentration change rate caused by evaporation, the concentration of the trivalent iron ions in the iron ions is preferably 5-60% by weight.
[0099] The concentration of the iron ions is preferably 1-80 g per 1 L of the electroplating solution, more preferably 10-50 g / L. When the concentration of the iron ions is less than 1 g / L, there is a problem of a sharp decrease in plating efficiency and plating quality. On the other hand, when the concentration of the iron ions exceeds 80 g / L, precipitation may occur due to the excess solubility, and the loss of raw materials caused by the loss of solution in the continuous plating process increases, which is uneconomical.
[0100] The electroplating solution of the present invention contains a complexing agent. In order to prevent sludge from being generated while containing a large amount of trivalent iron and to maintain high plating efficiency, it is preferred to use an amino acid or an amino acid polymer as the complexing agent.
[0101] Amino acid refers to an organic molecule formed by the combination of a carboxyl group (-COOH) and an amino group (-NH2), and an amino acid polymer refers to an organic molecule formed by the polymerization of two or more amino acids, and an amino acid polymer shows complexing agent properties similar to those of amino acids. Therefore, in the following description, amino acids and amino acid polymers are collectively referred to as amino acids.
[0102] When amino acids are dissolved in neutral water, the amines combine with hydrogen ions to become positively charged, while the hydrogen ions of the carboxyl groups are dissociated to become negatively charged, so the amino acid molecules remain electrically neutral. In addition, when the solution is acidified, the carboxyl groups and hydrogen ions are recombined to become electrically neutral, while the amines have a positive charge, so the amino acid molecules form positive ions. In other words, amino acids form electrically neutral or positive ions in slightly acidic aqueous solutions.
[0103] When amino acids are added to an acidic electrolyte containing iron ions, the amino acids complex with divalent iron ions and trivalent iron ions, and the iron ions complexed with the amino acids remain in a positive ion state even in the complex state. Therefore, compared with conventional complexing agents with multiple carboxyl groups that carry a negative charge in a weakly acidic aqueous solution, they exhibit opposite electrical properties.
[0104] In addition, compared with complexing agents containing multiple carboxyl groups such as citric acid and EDTA, amino acids form fewer bonds with iron ions and have weaker bonding strength, but the bonding strength with trivalent iron ions that produce sludge is strong enough, so precipitation caused by trivalent iron ions can be prevented. In addition, even if trivalent iron ions are complexed, positive ions can be maintained, so trivalent iron ions are easily transferred to the negative electrode and reduced to divalent iron ions, so that they can participate in the plating reaction. On the other hand, the movement to the positive electrode is suppressed, and the generation rate of trivalent iron ions is slowed down. Therefore, even if continuous plating is performed for a long time, the concentration of trivalent iron ions is maintained at a specified level, the specified plating efficiency is maintained, and there is no need to replace the electrolyte.
[0105] In addition, in the continuous electroplating process, when the iron ions in the plating solution are exhausted, the solution is acidified, and even if the same amount of iron ions are precipitated, the pH change of the solution containing trivalent iron ions is reduced compared to the solution containing only divalent iron ions. When the pH increases, part of the trivalent iron ions are combined with hydroxide ions, and when the pH decreases, the hydroxide ions are separated and neutralized. Therefore, even if the solution containing trivalent iron ions does not have a separate pH buffer, the pH change is also slowed down, thereby playing the role of a pH buffer, and therefore, the specified electroplating efficiency can be maintained in the continuous electroplating process.
[0106] Therefore, by using an amino acid as a chelating agent, sludge can be prevented, and not only divalent iron ions but also trivalent iron ions can be used as plating raw materials. When divalent iron ions and trivalent iron ions are mixed, the pH change of the solution can be slowed down and the accumulation of trivalent iron ions can be easily prevented. Therefore, the specified plating efficiency and plating quality can be maintained in the continuous electroplating process.
[0107] In addition, the complexing agent can be added so that the molar concentration ratio of the iron ion to the complexing agent is preferably 1:0.05 to 2.0, more preferably 1:0.5 to 1.0. When the above value is less than 0.05, it is impossible to suppress the excessive ferric ion contained to be combined with hydroxide ion or oxygen to form sludge, and even if ferric iron is not included, the plating efficiency is also greatly reduced, and then combustion can be caused, so the plating quality deteriorates. On the other hand, even if the above value exceeds 2.0, the sludge suppression effect and the plating quality can also be kept, but the overvoltage increases and the plating efficiency decreases, and compared with the raw material containing iron ion such as iron sulfate, it is unnecessary to include excessive relatively high-priced amino acids, so the raw material cost increases and is uneconomical.
[0108] The complexing agent is preferably one or more selected from amino acids or amino acid polymers, for example, one or more selected from alanine, glycine, serine, threonine, arginine, glutamine, glutamic acid and glycylglycine.
[0109] When the amino acid is used as a complexing agent and the solution temperature is maintained below 80°C and the pH is 2.0 to 5.0, the concentration of 3-120 A / dm 2 When electroplating is carried out at a current density of , an Fe plating layer with high plating efficiency and high oxygen concentration can be obtained.
[0110] Although the temperature of the Fe electroplating solution has little effect on the quality of the Fe plating layer, when the temperature of the Fe electroplating solution exceeds 80°C, the evaporation of the solution becomes serious, the concentration of the solution continues to change, and it is difficult to perform uniform electroplating.
[0111] When the pH of the Fe electroplating solution is less than 2.0, the electroplating efficiency is reduced and is not suitable for a continuous plating process. When the pH exceeds 5.0, although the plating efficiency is increased, sludge of iron hydroxide precipitation is generated during the continuous electroplating process, resulting in pipeline blockage, roller and equipment pollution.
[0112] When the current density is less than 3A / dm 2 When the current density exceeds 120A / dm 2 When the coating is heated, the coating surface burns, the coating becomes uneven, and the Fe coating easily falls off.
[0113] As described above, the present invention preferably contains 5-50 wt% oxygen in the Fe coating. The reason for the mixing of oxygen in the Fe coating is as follows. In the process of iron precipitation on the surface of the steel plate to which the negative electrode is applied, hydrogen ions are simultaneously reduced to hydrogen gas, and the pH rises. Therefore, both the divalent iron ions and the trivalent iron ions are temporarily combined with OH. - Ion combination, and can be mixed together when forming the Fe coating. If anionic complexing agents such as acetic acid, lactic acid, citric acid, EDTA, etc. are used, the complexing agent and OH - The ion-bound iron ions have an average negative charge, and when the negative electrode for electroplating is applied, an electric repulsion is generated, thereby inhibiting the mixing into the Fe plating layer. On the other hand, amino acids are electrically neutral at pH 2.0 to 5.0, and have positive ions in strong acids with a pH of less than 2.0. Even if the iron ions bound to amino acids have 1-2 OH groups, -, and also carry positive ions, so it generates electrical attraction with the negative electrode for electroplating and mixes a large amount of oxygen. Therefore, when Fe electroplating is performed using amino acids as complexing agents, with a molar concentration ratio of iron ions to amino acids of 1:0.05 to 1:2.0, and pH is maintained at 2.0 to 5.0, a Fe coating containing 5-50% by weight of oxygen can be obtained while having high plating efficiency and suppressing the generation of sludge.
[0114] In order to ensure the quality of hot-dip galvanizing of steel sheets containing Mn and Si, the concentration of iron is preferably 0.5-3.0 g / m 2 The upper limit of the Fe coating amount is not particularly limited, but when it exceeds 3.0 g / m 2 When the Fe plating amount is large, multiple plating units are required or the production speed is reduced, which is not economical. In addition, when the Fe plating amount is large, the Fe plating solution in the continuous process will be rapidly degenerated, resulting in a decrease in pH and a significant decrease in plating efficiency, which makes it difficult to manage the solution. On the other hand, when the Fe plating amount is less than 0.5 g / m 2 When the Fe coating is completely reduced during annealing, the oxygen contained in the Fe coating is rapidly reduced and removed, so it is not possible to effectively suppress the diffusion of Mn and Si from the base iron and the formation of surface oxides, resulting in a problem of reduced hot dip coating quality. The Fe coating amount is the iron concentration contained in the coating, and when the Fe coating is completely reduced during annealing, it has a thickness of about 0.05-0.4 μm.
Claims
1. A steel plate having a composition comprising Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, N: 0.01% or less, Cr: 1.5% or less, B: 0.005% or less, and the balance of Fe and inevitable impurities, The GDS curve of the Mn component and the GDS curve of the Si component observed from the surface in the depth direction contain a maximum point and a minimum point respectively. The difference between the value of the Mn concentration at the maximum point of the GDS curve of the Mn component divided by the Mn concentration of the base material and the value of the Mn concentration at the minimum point of the GDS curve of the Mn component divided by the Mn concentration of the base material, i.e., the Mn conversion concentration difference is 10% or more, The difference between the value of the Si concentration at the maximum point of the GDS curve of the Si component divided by the Si concentration of the base material and the value of the Si concentration at the minimum point of the GDS curve of the Si component divided by the Si concentration of the base material, i.e., the Si conversion concentration difference is 10% or more, in, When no local point appears within a depth of 5 μm, the position at a depth of 5 μm is regarded as the position where the local point appears.
2. The steel plate according to claim 1, wherein: The steel sheet includes a base iron and an Fe plating layer formed on a surface of the base iron, and the surface is a surface of the Fe plating layer.
3. The steel plate according to claim 1, wherein: The difference in the converted concentration of Mn is 15% or more, and the difference in the converted concentration of Si is 15% or more.
4. The steel plate according to claim 1, wherein: The maximum point is formed at a depth of 0.05-1.0 μm. 5 . A hot-dip galvanized steel sheet comprising the steel sheet for plating according to claim 1 , and a hot-dip galvanized layer formed on the steel sheet for plating.
6. A method for manufacturing a steel plate, comprising the following steps: preparing a base iron having a composition including, in weight %, Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, N: 0.01% or less, Cr: 1.5% or less, B: 0.005% or less, and the balance of Fe and inevitable impurities; Electroplating the substrate iron to form an Fe plating layer containing 5-50 wt % of oxygen; and The base iron on which the Fe plating layer is formed is annealed in an annealing furnace in an atmosphere of 1-70% H2-balance N2 gas with a dew point temperature controlled below -20°C at 600-950°C for 5-120 seconds.
7. The method for manufacturing a steel plate according to claim 6, wherein: The Fe coating has an adhesion of 0.5-3 g / m 2 .
8. The method for manufacturing a steel plate according to claim 6 or 7, wherein: The complexing agent is one or more selected from alanine, glycine, serine, threonine, arginine, glutamine, glutamic acid and glycylglycine.
9. The method for manufacturing a steel plate according to claim 6 or 7, wherein: The electroplating solution contains divalent iron ions and trivalent iron ions, the ratio of the trivalent iron ions to the total iron ions is 5-60 wt %, and the total concentration of the iron ions is 1-80 g per 1 L of the electroplating solution.
10. The method for manufacturing a steel plate according to claim 6 or 7, wherein: The electroplating process is carried out at a solution temperature of 80°C or less and a current density of 3-120A / dm 2 under the conditions of.
11. A method for manufacturing a hot-dip galvanized steel sheet, comprising the following steps: preparing a base iron having a composition including, in weight %, Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, N: 0.01% or less, Cr: 1.5% or less, B: 0.005% or less, and the balance of Fe and inevitable impurities; Electroplating the substrate iron to form an Fe coating containing 5-50 wt % of oxygen; Annealing the base iron on which the Fe plating layer is formed at 600-950° C. for 5-120 seconds in an annealing furnace in an atmosphere of 1-70% H 2 -balance N 2 gas with a dew point temperature controlled below −20° C., thereby obtaining a steel sheet for plating; and The steel sheet for coating is immersed in a galvanizing bath.
